Evidence for a cardiac metabolic switch in patients with Hodgkin's lymphoma - Heckmann, Markus B.; Totakhel, Belal; Finke, Daniel; Anker, Markus S.; Müller-Tidow, Carsten; Haberkorn, Uwe; Katus, Hugo; Lehmann, Lorenz (ESC heart failure, 2019)
Aims Our aim was to investigate the glucose uptake in cancer patients suffering from different entities, using 18F-FDG positron emission tomography-computed tomography scans. We further aimed at identifying potential variables altering cardiac and skeletal muscle glucose metabolism. Methods and results In a retrospective cohort study, we analysed cardiac and skeletal muscle 18F-FDG uptake in onco-positron emission tomography-computed tomography scans in adult patients suffering from Hodgkin's lymphoma, non-Hodgkin's lymphoma, and non-lymphatic cancer including patients suffering from thyroid cancer, bronchial carcinoma, and malignant melanoma. Univariate logistic regression models were created for increased cardiac and skeletal muscle 18F-FDG uptake using cancer entity, sex, age, previous radiation, previous chemotherapy, diabetes, obesity, serum glucose levels, renal function, and thyroid function as parameters. Multivariate models were created by selecting variables according to Akaike's information criterion in a step-down approach. Between 2014 and 2018, a total of 337 consecutive patients suffering from Hodgkin's lymphoma (n = 52), non-Hodgkin's lymphoma (n = 57), and non-lymphatic cancer (n = 228) were included in the analysis. Univariate logistic regression models showed high serum glucose levels to be associated with lower absorption rates in both cardiac and skeletal muscle (odds ratio [OR] 0.38 [0.23, 0.60, 95% confidence interval—CI], P < 0.0001, and 0.52 [0.33, 0.82, 95% CI], P < 0.005, respectively). Hodgkin's lymphoma was associated with an increase in cardiac uptake (OR 2.4 [1.3, 4.5, 95% CI], P < 0.005). Decreased skeletal muscle 18F-FDG uptake was noted in elderly and obese patients. In our multivariate analysis, Hodgkin's lymphoma patients showed higher cardiac 18F-FDG uptake, while non-Hodgkin's lymphoma patients did not differ significantly from non-lymphatic cancer patients (OR 1.6 [0.7, 3.3, 95% CI], P = 0.24). High serum glucose levels and prior chemotherapy were both associated with a significantly decreased cardiac 18F-FDG uptake (OR 0.40 [0.24, 0.65, 95% CI], P < 0.0005, and 0.50 [0.27, 0.90, 95% CI], P < 0.05, respectively). Notably, prior chemotherapy did not influence FDG uptake in skeletal muscle to the same extent. Obesity and older age were both significantly associated with decreased gluteal 18F-FDG uptake (OR 0.49 [0.27, 0.89, 95% CI], P < 0.05, and 0.47 [0.25, 0.87, 95% CI], P < 0.05). Conclusions Our data provide evidence for metabolic alterations in patients with Hodgkin's lymphoma related to cardiac glucose uptake in humans. This effect was independent from skeletal muscle metabolism.
First published: 06 July 2019
Gesehen am 19.05.2020